Pengembangan Panduan Praktikum Laboratorium Virtual Berbasis Keterampilan Proses Sains Untuk Meningkatkan Pemahaman Konsep Siswa - Anggraini, Dini; Suseno, Nyoto; Alarifin, Dedy Hidayatullah (Universitas Muhammadiyah Metro, 2020)
ABSTRACTEfforts to improve understanding of concepts in students can be seen from their academic abilities. Understanding concepts is a term used to mean the extent to which students are able to understand the basic concepts of a material provided by the teacher. One effort to improve the understanding of concepts in students is to do experimental learning models or practicum. Along with the advancement of time where technology can be used as a tool in learning, therefore the implementation of practicum can be done using a virtual laboratory. The use of virtual laboratories can run well and in accordance with procedures when using a virtual laboratory practicum guidelines. The making of practicum guidelines must not be separated from the scientific process skills because it has been regulated in Regulation of the Ministry of Education and Culture No. 22 of2016.The purpose of this study is to find out the development of practical process guidelines based on science process skills using virtual laboratories, to determine the impact of virtual laboratories on students' understanding of concepts, and to determine the strengths and weaknesses of virtual laboratories. After conducting field tests in SMA 1 Metro with a class XII IPA 4 as sample, it is known that the results of the feasibility of using a virtual laboratory practice guidelines based on science process skills, namely expert validation got a percentage of 84.6%, Teacher Response 91.25% and Student Response 88, 4% Based on the average percentage of the three assessments of 88.08%, it is in the very feasible category. As for understanding the concept an increase of 21.4 between the pretest and posttest scores. Based on the results of the study, the virtual laboratory practicum guidelines based on science process skills affect the learning process specifically to improve students' understanding of concepts. Keywords: Development of practicum guides, virtual laboratories, science process skills, conceptual understanding